Wurst Storm Rising - Graham St John; Botond Vitos (Journal of Festive Studies)
Our subject is the legacy of Dada implicit to the Burning Man phenomenon. Animate in the provocative output of fin-de-siècle French Symbolist writer and puppeteer Alfred Jarry, and filtered through the antics of the San Francisco Cacophony Society, Dada is foundational to the cultural aesthetic of Burning Man, by which we mean the event in Nevada’s Black Rock Desert playa (Black Rock City) and a global network of “burn” events. We address the significance of the Cacophony Society expedition that inaugurated the desert phase of Burning Man in 1990, “Zone Trip # 4: Bad Day at Black Rock.” Integral to the surreal tourism ventured by Cacophonists prior to the inception of Burning Man, and pivotal to its desert phase, the Zone Trip kindled “Burner” culture on the Black Rock playa and abroad. Exploring the Dadaist impulse affecting Black Rock City and woven into a worldwide network, informed by interpretative and applied methods, the article addresses art projects (including those designed and implemented by Vitos) at three regional events—Israel’s Midburn and Germany’s Burning Bär and Kiez Burn—visited in 2018 and 2019 as part of a multisited ethnography of the Burning Man movement. As these projects illustrate, the ghost of Jarry haunts, as the spirit of Dada animates, the transnational “burnscape.”